Accounting Practices in the Utilization of Heritage Assets: A Case Study of the Villa Yuliana Museum at the Department of Education and Culture, Soppeng Regency - Andi Muhammad Nurul Afdhal; Nur Achriaty Achmar; Ayu Lestari Amda (GENTARA: management and accounting research, 2026)
Heritage assets represent national wealth in the form of cultural heritage sites, monuments, and historic buildings that are unique, fragile, rare, and non-renewable. As such, the preservation and management of these assets must be carried out in an integrated manner, considering both cultural and economic aspects. One strategy for preserving and managing heritage assets is through their utilization as tourism and educational facilities, aimed at increasing local revenue (Pendapatan Asli Daerah/PAD) through the collection of retribution fees. This study seeks to examine the implementation of accounting practices related to retribution revenue from the utilization of a heritage asset, namely the Villa Yuliana Museum, under the authority of the Department of Education and Culture in Soppeng Regency. The analysis focuses on four key aspects of accounting: recognition, measurement, presentation, and disclosure. Data collection methods employed in this research include interviews, observation, documentation, and literature review. The data were analyzed using a qualitative descriptive approach. The findings indicate that the accounting treatment of retribution revenue from the utilization of the Villa Yuliana Museum aligns with the relevant accounting policies and applicable regulations. Furthermore, the determination of retribution rates is consistent with prevailing legal standards